The Role of Percutaneous Ventricular Restoration Therapy in Heart Failure After Myocardial Infarction - Yudhie Tanta; Ali Ghanie; Taufik Indrajaya; Erwin Sukandi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
The process of ventricular remodeling has a major role in the pathogenesis of heart failure in patients with myocardial infarction. Angiotensin-converting enzyme (ACE) inhibitors, angiotensin receptor blockers (ARBs), antialdosterone diuretics, and beta receptor blockers are drugs that have been widely accepted as anti-remodeling agents. However, sometimes the efficacy of these drugs is inadequate, or their use is constrained by low blood pressure. Percutaneous ventricular restoration therapy is an action that aims to exclude segments of the myocardium that have akinetic or aneurysms by implanting a ventricular partitioning device percutaneously. This technique is expected to prevent the progression of ventricular remodeling through a procedure with a lower risk of intraprocedural mortality than the surgical approach.